Humour and Cruelty. Laughing Matters Prolegomena - Baruchello, Giorgio (De Gruyter Studies in Philosophy of Humor, 2023)
The present book addresses the background, rationale, general structure, and particular aims and arguments characterizing our third and last volume about "humor" and "cruelty". A guiding foray is provided into the vast expert literature that can be retrieved in the Western humanities and social sciences on these two terms. Pivotal thinkers and crucial notions are duly identified, highlighted, and examined. Apposite subsidiary references are also included, especially with regard to psychodynamics and clinical psychology, existentialism, feminism, liberalism, Marxism, and representative recent studies in the philosophy of humor and its cognates. The stage is thus set for the exploration and assessment of the conflicts between humor and cruelty unfolding in Part 2 of Volume 3. Being the philosophical terminus of our entire research project, Volume 3 counterbalances, complements, and, occasionally, complexifies the numerous forms of mutual cooperation between humor and cruelty that the preceding Volume 2 had unearthed and discussed